Refracting schoolgirls: pedagogical intra-actions producing shame. Issue 5 (3rd September 2017) - Wolfe, Melissa Joy
ABSTRACT: This article contributes to the discussion of gender inequality in schools with the central theme tracing ways that pedagogical affect im/mobilises agency. I argue that what I call 'the schoolgirl affect', as distinctly gendered pedagogical practices in schools, constitute a schoolgirl body that refracts capacity for action in particular ways. Karen Barad's theorising of performativity allows me to move away from a definition of what schoolgirl success is and rather discuss ways successful schoolgirls are co-constructed. Using filmed testimonial accounts of former Australian schoolgirls, I attempt to understand how practices of shaming inhibit interest and in fact stultify these students in a myriad of ways. I consider if shame when recognised as materially discursive results in a complex affirmative repositioning that is productive of agency. I interrogate ways that the shame/interest pendulum may affectively constitute schoolgirls, influence ethical educational practices and impact the life trajectories of these particular schoolgirls.